Cultural Identity Awareness of Hmong Students in Higher Education at the University of Wisconsin--Eau Claire - Yang, Mee (My University, 2011)
This study gives an overview of how Hmong students at the University of Wisconsin--Eau Claire view their cultural identity.
Color poster with text and photographs.
Keywords: Hmong Americans--Ethnic identity; Hmong Americans--Social life and customs; University of Wisconsin--Eau Claire--Students; Posters